STRATEGI PERBAIKAN KEMASAN PRODUK BERAS SEHAT SEBAGAI MEDIA PROMOSI KAMPUNG WISATA TEMATIK MULYAHARJA - Gayatri Anggarkasih, Made; Early Febrinda, Andi; Imas Faidoh Fatimah, Ai; Zaim Adzkiya, M. Agung; Mariyani, Neny; Lukie Trianawati, Mrr.; Yuni Hastati, Dwi; Sarastani, Dewi; Dyah Hapsari, Rianti; Razna Suhaima, Nurafi; Irhamni Fajri, Aulia; Putri Salshabila, Lintang; Fatimah Madania, Kanaya; Fidella, Aliya (Jurnal Abdi Insani, 2024)
Mulyaharja Village, South Bogor, has an organic agrotourism destination called AEWO Mulyaharja. KTD Lemah Duhur, a local farmer group, produces organic rice and healthy rice. Organic rice has been certified and packaged well. However, healthy rice which is more productive than organic rice does not yet have good packaging and labeling. This community service aims to improve the quality and marketing of healthy rice through vacuum packaging and informative labeling. This study involved surveys, focus group discussions, laboratory experiments, and the design of attractive and informative labels. Results showed that vacuum packaging effectively maintained the quality of rice and the new label increased the appeal of the product and could be a promotional medium for AEWO Mulyaharja. However, higher production costs due to vacuum packaging led to elevated selling prices, which affected consumer interest. This study recommends further research on cost-effective packaging materials and exploring potential markets for premium-priced healthy rice products.